The interrelationships between corporate political activity and corporate environmental performance: the role of language diversity - Shoham, Amir; Frynas, Jedrzej George; Arslan, Ahmad; Bazel-Shoham, Ofra; Lee, Sang Mook; Khan, Zaheer; Tarba, Shlomo (Journal of International Business Studies, 2024)
Abstract Language affects almost every aspect of management in multinational enterprises (MNEs) but little is known about the impact of language on environmental performance. Our study investigates how language diversity affects the environmental performance of MNEs worldwide. We show that the grammatical structure of a language – specifically the first pronoun drop – is an important factor explaining the environmental performance of firms. Our analysis of 4454 company-year observations suggests that MNEs operating in societies that permit the first pronoun drop tend to have better environmental performance. Furthermore, we explore the impact of linguistic structure on the relationship between environmental performance and corporate political activity (CPA). We find that using the first pronoun drop of the local language moderates the influence of CPA on firms’ environmental performance. Our study concludes that international managers must pay greater attention to the neglected role of language in implementing environmental initiatives.